Optimization of phosphorus removal in secondary effluent using immersed ultrafiltration membranes with in-line coagulant pretreatment — implications for advanced water treatment and reuse applications. Issue 3 (1st November 2013) - Kent, Fraser; Farahbakhsh, Khosrow; Citulski, Joel
Abstract : In-line addition of alum and ferric chloride was conducted at a hollow-fibre immersed ultrafiltration (UF) membrane pilot plant, using secondary effluent from a municipal wastewater treatment plant (WWTP) as the feed. The objective of such pretreatment was to remove phosphorus from the feed from an initial concentration of approximately 5  mg/L to below 0·3  mg/L. The simplified in-line coagulant addition process involved hydraulic mixing of the coagulant into the feed and subsequent flocculation, and a greatly reduced (12  –  14  min) flocculation time relative to conventional coagulation-flocculation-settling treatment. Both alum and ferric chloride effectively removed phosphorus to below the 0·3  mg/L threshold when applied as a pretreatment at optimized doses, both of which were below the WWTP's current coagulant dose (as ferrous chloride). This simplified pre-treatment scheme provided consistent enhanced removal of phosphorus and organic compounds. These results suggest that simplified in-line coagulant addition in advance of immersed UF membranes enhances the ability to produce treated effluent suitable for water-reuse applications.